Seasonal distribution of antibiotic resistance genes in the Yellow River water and tap water, and their potential transmission from water to human. (1st January 2022) - Yu, Qiaoling; Feng, Tianshu; Yang, Jiawei; Su, Wanghong; Zhou, Rui; Wang, Yijie; Zhang, Hong; Li, Huan
Abstract: The prevalence and transmission of antibiotic resistance genes (ARGs) and opportunistic pathogens in water environments can pose great threat to public health. However, the dissemination of ARGs and opportunistic pathogens from water environments to humans has been poorly explored. Here, we employed 16S rRNA gene sequencing and high-throughput quantitative PCR techniques to explore the seasonal distribution of ARGs and opportunistic pathogens in the Yellow River water (source water) and tap water, as well as their relationships with healthy humans at Lanzhou, China. Physiochemical analysis was applied to detect water quality parameters and heavy metal contents. The absolute abundance and diversity of ARGs in the Yellow River and tap water demonstrated distinct seasonal patterns. In winter, the Yellow river water had the highest ARG abundance and diversity, while tap water owned the lowest. Mobile genetic elements (MGEs) were the predominant driver of ARG profiles in both the Yellow river and tap water. Null model analysis showed that ARG assembly in the Yellow River was more influenced by stochastic processes than tap water and this was independent of seasons. Total organic carbon and arsenic contents exhibited positive correlations with many ARGs. Opportunistic pathogens Aeromonas and Pseudomonas may be potential hosts for ARGs. Approximately 80% of detected ARGs were shared between water samples and the human gut. These persistent ARGs could not be entirely eliminated through drinking water treatment processes. Thus, it is crucial to protect sources of tap water from anthropogenic pollution and improve water treatment technologies to reduce the dissemination of ARGs and ensure drinking-water biosafety for human health. Graphical abstract: Image 1 Highlights: The ARG profiles in the Yellow River and tap water had distinct seasonal patterns. MGEs were the key driver for ARG profiles in the Yellow River and tap water. ARGs assembly in the Yellow River had more stochastic processes. Opportunistic pathogens Aeromonas and Pseudomonas may be potential hosts for ARGs. Persistent ARGs cannot be entirely eliminated via drinking water treatment process.